Prognostic value of [18F]FDG-PET/CT in multiple myeloma patients before and after allogeneic hematopoietic cell transplantation - Stolzenburg, Antje; Lückerath, Katharina; Samnick, Samuel; Speer, Martin; Kneer, Katharina; Schmid, Jan-Stefan; Grigoleit, Götz Ulrich; Hofmann, Susanne; Beer, Ambros; Bunjes, Donald; Knop, Stefan; Buck, Andreas K.; et al. (European journal of nuclear medicine and molecular imaging, 2018)
Despite improved treatment options, multiple myeloma (MM) remains an incurable disease. The aim of this study was to investigate the prognostic value of positron emission tomography/computed tomography (PET/CT) using 18F-2’-deoxy-2’-fluorodeoxyglucose ([18F]FDG) in MM patients shortly before and ~100 days after allogeneic hematopoietic cell transplantation (allo-HCT).
Gesehen am 21.04.2020